Location factors and ecosystem embedding of sustainability-engaged blockchain companies in the US: A web-based analysis - Jan Kinne; Robert Dehghan; Sebastian Schmidt; David Lenz; Hanna Hottenrott (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2024)
While many digital technologies provide opportunities for creating business models with an impact on sustainability, some technologies, especially blockchain applications, are often criticized for harming the environment, e.g. due to high energy demand. In our study, we present a novel approach to identify sustainability-focused blockchain companies and relate their level of engagement to location factors and entrepreneurial ecosystem embeddedness. For this, we use a large-scale web scraping approach to analyze the textual content and hyperlink networks of all US companies from their websites. Our results show that blockchain remains a niche technology, with its use communicated by about 0.6% of US companies. However, the proportion of sustainable blockchain firms is significantly higher than in the overall firm population. Additionally, we find that blockchain companies with an intensified focus on sustainability have, at least quantitatively, a more intensive embedding in entrepreneurial ecosystems, while infrastructural and socio-economic location factors hardly play a role.
Keywords: Q56; R30; L86; 330; sustainability; blockchain; ecosystem; location factors; natural language processing